Analisis Perbandingan Kinerja Saham Syariah dan Saham Konvensional Berdasarkan Return, Rasio Sharpe, Rasio Jensen dan Rasio Treynor di Sektor Manufaktur Bursa Efek Indonesia - Muhammad Andryzal Fajar (STIE Pelita Nusantara Semarang, 2020)
The study aims to determine the difference in performance of Islamic stock with conventional stock in Indonesia. The aspects investigated through performance returns and measurement of risk adjusted returns. The measurement of risk adjusted return uses sharpe ratio, Jensen ratio, and treynor ratio. This research is a comparative descriptive. Sampling uses purposive sampling so that selected criteria that meet 24 sharia stocks and 27 conventional stock in the BEI manufacturing sector during the period 2016-2018. The data used are secondary data in the form of islamic and conventional stock prices. Data were analyzed using the Independent Sample T-test and Mann-Whitney U-Test. The results showed the mean Return, Sharpe ratio and Jensen ratio of islamic stocks were lower than conventional stock while the average Treynor ratio of islamic stock was higher than conventional stock. Based on the different Independent Sample T-test and Mann-Whitney U-Test measures of performance through returns, Sharpe ratios, Jensen ratios and Treynor ratios there was no significant difference between islamic stock compared to conventional stock in the manufacturing sector on Indonesia Stock Exchange